Design and implementation of a series of activities to develop the listening skills of the attendees of the english conversation club - intermediate level at Universidad del Valle (2019)
Developing listening skills is a daunting task for most foreign language students. It brings about anxiety and learners may feel stressed out over aspects like fluency and pronunciation. However, it is through practice that learners overcome anxiety and start to process the language they heat more easily. This study aims to put forward a set of series activities that will serve the purpose of promoting the development of the listening skills in the context of the English conversation club- Intermediate level at Universidad del Valle. Conducted through an action research approach, this project was implemented in two stages: stage one featured the gathering of the data which would allow to determine the students’’ learning needs and interest (from which the research subject arose) while stage two was the implementation of weekly teaching sequences. It was one academic year and had positive results as per the assessment method used. Attendees completed a survey on a weekly basis which allowed to measure the impact that the activities had towards achieving the study’s main goals.